2019
DOI: 10.3390/jcm8050643
|View full text |Cite
|
Sign up to set email alerts
|

Exhalative Breath Markers Do Not Offer for Diagnosis of Interstitial Lung Diseases: Data from the European IPF Registry (eurIPFreg) and Biobank

Abstract: Background: New biomarkers are urgently needed to facilitate diagnosis in Interstitial Lung Diseases (ILD), thus reducing the need for invasive procedures, and to enable tailoring and monitoring of medical treatment. Methods: In this study we investigated if patients with idiopathic pulmonary fibrosis (IPF; n = 21), non-IPF ILDs (n = 57) and other lung diseases (chronic obstructive pulmonary disease (COPD) n = 24, lung cancer (LC) n = 16) as well as healthy subjects (n = 20) show relevant differences in exhale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
8
1
2
Order By: Relevance
“…Despite higher serum and EBC TSLP levels in IPF patients when compared to controls in that study, the concentrations of TSLP in these two materials did not correlate [20]. Krauss et al also did not find relationships between EBC and BALF concentrations of PGE2 and 8-isoprostane in patients with different interstitial lung diseases, including IPF [25]. Therefore, we believe that cytokine level measurements in serum, BALF and sputum should not be extrapolated to EBC in patients with IPF.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Despite higher serum and EBC TSLP levels in IPF patients when compared to controls in that study, the concentrations of TSLP in these two materials did not correlate [20]. Krauss et al also did not find relationships between EBC and BALF concentrations of PGE2 and 8-isoprostane in patients with different interstitial lung diseases, including IPF [25]. Therefore, we believe that cytokine level measurements in serum, BALF and sputum should not be extrapolated to EBC in patients with IPF.…”
Section: Discussioncontrasting
confidence: 57%
“…Although a previous report showed that EBC analysis might modestly contribute to the diagnosis and monitoring of IPF [25], some authors demonstrated that EBC composition might discriminate between IPF patients and control subjects [20,26]. It seems that these equivocal findings may result from the complex cytokine interplay in the pathogenesis of IPF and a (still) insufficient knowledge of the specific cytokines involved.…”
Section: Discussionmentioning
confidence: 98%
“…In some cases, e.g., IPF, the patient’s survival might be still limited despite novel antifibrotic therapies [7,8]. Although significant progress in the understanding of the pathogenesis of ILDs has been made, the natural course, progression factors, biomarkers, and the response to the treatment of an individual patient still cannot be reliably predicted [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The potential value of eNO in the differential diagnosis of IPF is surely intriguing, but still largely unexplored. Few studies have been specifically designed to investigate the potential value of eNO parameters in the differential diagnosis of ILDs [ 7 , 8 , 51 , 55 ]. Among these, the papers by Oishi et al and Cameli et al were the only ones to implement multiple-flows eNO assessment in their studies.…”
Section: Extended Feno Analysis In Ilds: Current Evidencementioning
confidence: 99%
“…Therefore, FeNO appears not to be reliable for the evaluation of NO production, and generally of inflammatory processes involving distal airways or alveolar spaces. Accordingly, conflicting results has been published concerning the significance of FeNO in respiratory diseases characterized by a more prominent involvement of peripheral districts, such as chronic obstructive pulmonary disease (COPD) or interstitial lung diseases (ILD) [ 5 , 6 , 7 , 8 ]. In order to overcome these limits, the extended analysis of FeNO, able to discriminate between bronchial and alveolar origins of eNO, have been repeatedly reported in the last decade, till the last technical standard document by ERS officially endorsed this procedure for future research [ 9 ].…”
Section: Introductionmentioning
confidence: 99%